A qualitative approach to experiential knowledge identified in focus groups aimed at co-designing a provocation test in the study of electrohypersensitivity. (31st December 2022) - Bordarie, Jimmy; Dieudonné, Maël; Ledent, Maryse; Prignot, Nicolas
Abstract: Patients' experiential knowledge is increasingly recognised as valuable for biomedical research. Its contribution can reveal unexplored aspects of their illnesses and allows research priorities to be refined according to theirs. It can also be argued that patients' experiential knowledge can contribute to biomedical research, by extending it to the most organic aspects of diseases. A few examples of collaboration between medicine and patient associations are promising, even if there is no single, simple methodology to apply. This article provides feedback on a project involving the experiential knowledge of electrohypersensitive persons with a view to developing an experimental protocol to study their condition. It presents the participatory approach with focus groups that was implemented and reflects on ways to take advantage of experiential knowledge. It also demonstrates the complexity of the electrohypersensitivity syndrome and reflects on the difficult transition between the experiential knowledge and the experimental design of provocation studies. KEY MESSAGES: Experiential knowledge is a valuable source of information for research and the design of investigation protocols. The participatory approach allows co-designing protocols by drawing on experiential knowledge. The controversial dimension of EHS reveals the complexity of translating experiential knowledge into an experimental protocol.